Why drawing, now?. (1st September 2014) - Douglas, Anne; Ravetz, Amanda; Genever, Kate; Siebers, Johan
This article takes the question 'why drawing, now?' as a speculative way to enter the debate on the relationship of art to different understandings of community. Drawing offers a paradox around the place of art in society. Drawing can be thought about as a traditional medium that yields an individually focused interior exploration. It has also performed a social or ritual role historically, in different times and places. Imagine a public event to which participants are invited to draw. There is a large, single sheet of paper or drawing surface and the offer of different drawing implements. Participants respond by drawing with their own style and understanding of what drawing is. The accumulation of individual marks and imaginations make up a whole, in as far as the surface drawn upon is singular and brings these individual productions into one space. Imagine the same shared drawing surface, held up around the edges by a group of participants. A drawing emerges through the marks of an inked ball rolling across the flexible moving surface. In this scenario, the drawing traces – literally marks – the emergent relationship of one individual to another through the shared activity. Both scenarios are possibly very familiar activities in participatory art practices and each offers a different way of imagining community. In both, the act of drawing is pivotal to shared activity. The first assumes that community can be constructed by bringing a group of individuals into the same space and activity. Many of us are enculturated to think that it is individuals – singular units – that make up society. The second, however, suggests that community as already present can be made visible through the drawing activity. Our exploration draws on a period of a collaborative practice-led experimentation, in particular a three-day research workshop involving drawing and writing. The aim was not to focus on what the results 'looked like' as art products, an approach that arguably fails to reveal the knowledge underpinning art's appearances. Instead we set out to create the conditions for experiencing community through drawing. We found that drawing, in its most intimate relationship between maker/viewer, surface and mark, evokes a world to come, a world in formation rather than pre-formed. This revealed the need for careful scrutiny of the ways in which community itself is imagined. Our offer to the practice of participatory arts is to question deeply held assumptions about what community is rather than to propose new forms of access or techniques that can be transferred from one situation to another.